2020
DOI: 10.1186/s12967-020-02362-4
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial impact of epigallocatechingallate on LDL-C through PCSK9/LDLR pathway by blocking HNF1α and activating FoxO3a

Abstract: Background: Green tea drinking has been proven to lower lipid and exert cardiovascular protection, while the potential mechanism has not been fully determined. This study was to investigate whether the beneficial impact of epigallocatechingallate (EGCG), a type of catechin in green tea on lipids is associated with proprotein convertase subtilisin/kexin type 9 (PCSK9) pathways. Methods: We studied the effects and underlying molecular mechanism of EGCG or green tea on regulating cholesterol from human, animal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 52 publications
(59 reference statements)
1
23
0
Order By: Relevance
“…Substantial evidence suggests that EGCG elicit a wide range of properties, including antioxidant and antilipid deposition and anti-inflammation [141][142][143]. Extensive studies have shown that the consumption of EGCG exhibited an LDL-C reducing effect [144][145][146][147]. A systematic review found that EGCG could significantly decrease the plasma LDL-C level at doses between 107 and 856 mg/d [148][149][150].…”
Section: Flavan-3-olsmentioning
confidence: 99%
“…Substantial evidence suggests that EGCG elicit a wide range of properties, including antioxidant and antilipid deposition and anti-inflammation [141][142][143]. Extensive studies have shown that the consumption of EGCG exhibited an LDL-C reducing effect [144][145][146][147]. A systematic review found that EGCG could significantly decrease the plasma LDL-C level at doses between 107 and 856 mg/d [148][149][150].…”
Section: Flavan-3-olsmentioning
confidence: 99%
“…LDLR ablation causes hypercholesterolemia when given a normal diet, confirming increased LDLR plays important roles in hypocholesterolemic effect (Guo et al., 2018). In addition, it has been reported that green tea extract or EGCG decreases cholesterol by LDLR induction (Bursill et al., 2007; Cui et al., 2020). A recent study has reported that Bacillus ‐fermented green tea reduces plasma TG through suppression of pancreatic lipase and boosting of the energy expenditure of rats and hamsters (Seo et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that EGCG lowered LDL levels of rats. [ 120 ] Liver X Receptor (LXR) is an important regulator of cholesterol homeostasis and lipid metabolism. Besides, it decreases the transcription of pro‐inflammatory genes.…”
Section: Discussionmentioning
confidence: 99%